A direction-tunable shear horizontal mode array magnetostrictive patch transducer. (July 2018) - Liu, Zenghua; Zhang, Yongchen; Xie, Muwen; Li, Aili; Bin, Wu; He, Cunfu
Abstract: Due to the simple wave structure and low-attenuation and non-dispersive properties, the lowest-order shear horizontal mode SH0 can realize the efficient large-scale damage detection in plate structures and shows a great application potential in non-destructive testing and structural health monitoring. In order to excite SH0 mode in aluminum plates, a direction-tunable shear-horizontal mode array magnetostrictive patch transducer (DT-SHMA-MPT) is developed based on the magnetostrictive effect. The proposed DT-SHMA-MPT consists of a transducer sleeve, four identical planar fan-shaped meander coils, four identical fan-shaped NdFeB permanent magnets, and a circular nickel patch. Four identical planar fan-shaped meander coils are connected in parallel to form a meander coil array. These planar fan-shaped meander coils are double-layer structures and made of flexible printed circuit (FPC). The experimental results show that the developed DT-SHMA-MPT can effectively excite and receive a single SH0 mode in aluminum plates. For the DT-SHMA-MPT with n planar fan-shaped meander coils and n fan-shaped permanent magnets ( n = 4, 3, 2), its frequency response characteristics are tested at the center frequencies of 775 kHz, 780 kHz, and 783 kHz, which are close to the predicted value. Furthermore, the effects of the number of fan-shaped meander coils and corresponding permanent magnets on the directivity of the transducer are also investigated. The acoustic field distribution or the directivity of the transducer directly depends on the number of fan-shaped meander coils and permanent magnets. Finally, the direction tuning of proposed transducer is investigated. The ability of excitation and reception of this transducer can be controlled by tuning the directional arrangement of fan-shaped meander coils and permanent magnets.